The Role of Pseudo-Orthocaspase (SyOC) of Synechocystis sp. PCC 6803 in Attenuating the Effect of Oxidative Stress - Lema A, Saul; Klemenčič, Marina; Völlmy, Franziska; Altelaar, Maarten; Funk, Christiane (Frontiers in Microbiology, 2021)
Caspases are proteases, best known for their involvement in the execution of apoptosis—a subtype of programmed cell death, which occurs only in animals. These proteases are composed of two structural building blocks: a proteolytically active p20 domain and a regulatory p10 domain. Although structural homologs appear in representatives of all other organisms, their functional homology, i.e., cell death depending on their proteolytical activity, is still much disputed. Additionally, pseudo-caspases and pseudo-metacaspases, in which the catalytic histidine-cysteine dyad is substituted with non-proteolytic amino acid residues, were shown to be involved in cell death programs. Here, we present the involvement of a pseudo-orthocaspase (SyOC), a prokaryotic caspase-homolog lacking the p10 domain, in oxidative stress in the model cyanobacterium Synechocystis sp. PCC 6803. To study the in vivo impact of this pseudo-protease during oxidative stress its gene expression during exposure to H2O2 was monitored by RT-qPCR. Furthermore, a knock-out mutant lacking the pseudo-orthocaspase gene was designed, and its survival and growth rates were compared to wild type cells as well as its proteome. Deletion of SyOC led to cells with a higher tolerance toward oxidative stress, suggesting that this protein may be involved in a pro-death pathway.